Propiedades psicométricas de la Escala de Satisfacción con la Vida en Para atletas Brasileños - Leite Rodrigues Melo, Geiziane; Leite Dias, Claudia; Almeida Ramos , Isabela; Ferreira Brandão, Maria Regina; Winckler, Ciro (Cuadernos de Psicología del Deporte, 2023)
The Satisfaction with Life Scale (SWLS) is an instrument that assesses subjective well-being in relation to life that was originally proposed in the English language. To analyze the psychometric properties do the SWLS for use with Para athletes. A convenience sample of 309 Brazilian Paralympic athletes (age: 33.08 ± 9.85 years) of both sexes was chosen. We conducted an online survey, and participants completed an anamnesis and SWLS questionnaires using the Qualtrics® software. To analyze confirmatory, the comparison fit index (CFI), the Tucker-Lewis index (TLI) and the standardized root mean square residual (SRMR) were used. Reliability was estimated by the ordinal alpha and omega coefficients. A multigroup analysis estimates a factor invariance. Exploratory and confirmatory factor analysis supported a single factor structure for the SWLS, with an acceptable fit. Cronbach’s α (0.88) and McDonald’s Omega (0.88) were indicative of internal consistency. Factorial invariance across gender, impairment, sports, and competition level was confirmed. The Brazilian version of the SWLS for Para athletes showed satisfactory psychometric properties and can be used to measure life satisfaction in the Paralympic context.